2020
DOI: 10.1039/c9se00691e
|View full text |Cite
|
Sign up to set email alerts
|

An MOF-derived C@NiO@Ni electrocatalyst for N2conversion to NH3in alkaline electrolytes

Abstract: MOF-derived C@NiO@Ni are proposed as an efficient electrocatalyst for N2 reduction reaction in alkaline media. Abundant oxygen vacancies and NiO/Ni interfaces can act as active sites for adsorbing nitrogen and proton, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Recently, Luo et al. found that MOF‐derived C@NiO@Ni microtubes (Figure a,3b) perform well in NRR, reaching both a high NH 3 yield rate of 43.15 μg h −1 mg cat −1 and a FE of 10.9% at −0.7 V (Figure c) …”
Section: Advances In Noble‐metal‐free Catalysts For Electrocatalyticmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, Luo et al. found that MOF‐derived C@NiO@Ni microtubes (Figure a,3b) perform well in NRR, reaching both a high NH 3 yield rate of 43.15 μg h −1 mg cat −1 and a FE of 10.9% at −0.7 V (Figure c) …”
Section: Advances In Noble‐metal‐free Catalysts For Electrocatalyticmentioning
confidence: 89%
“…[70] Five prototypical MOFs, Fe based-ZIF-8(Fe), [71] Co-based ZIF-67(Co), [72] PCN-222(Fe), [73] Cu II À MOF, [74] HKUST-1 (Cu-benzene-1,3,5-tricarboxylate) [75] were investigated, demonstrating the highest performance with NH 3 [76] Recently, Luo et al found that MOF-derived C@NiO@Ni microtubes (Figure 3a,3b) perform well in NRR, reaching both a high NH 3 yield rate of 43.15 μg h À 1 mg cat À 1 and a FE of 10.9% at À 0.7 V (Figure 3c). [77] The rich 3D interconnected porous structure of MOFs is conducive to the enrichment and diffusion of reactant nitrogen molecules, and a large number of atomic distribution metal ions as a Lewis acid in MOFs is considered as the active sites, which can withdraw p electrons from N 2 molecules and weaken the N � N bonds. However, no other MOFs for electrochemical NRR have been reported so far, and in particular, MOFs with high conductivity as well as water stability are one of the development directions in future studies.…”
Section: Mof Based Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was found that a synergetic effect between the N-doped carbon and Co 3 O 4 accounts for the good NRR activity, resulting in FE of 8.5% [ 38 ]. Lu et al fabricated Ni-based MOF-derived C@NiO@Ni microtubes that exhibited NH 3 FE of 11% [ 71 ]. Wang et al rationally designed an Fe-N/C NRR catalyst reaching NH3 FE of 9.2%, by carbonization of a Fe-ZIF-8-CNTs precursor at 1000 °C [ 55 ].…”
Section: Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 99%
“…Luo and co‐workers fabricated C@NiO@Ni which was derived by metal organic framework. [ 194 ] On investigating it as electrocatalyst for NRR in 0.1 m KOH, at −0.7 V, it delivered NH 3 at bulk rate (43.15 µg h −1 mg cat −1 ) with very high faradaic efficiency (10.9%). The magnificent activity of C@NiO@Ni was ascribed to abundant oxygen vacancies and high NiO@Ni interface, which collectively improved N 2 selectivity and proton adsorption resulting in enhanced NRR activity.…”
Section: Transition Metals or Elementsmentioning
confidence: 99%